The neurological symptoms of COVID-19: a systematic overview of systematic reviews, comparison with other neurological conditions and implications for healthcare services - Tamar Wildwing; Nicole Holt (SAGE Publishing, 2021)
Aims: In response to the rapid spread of COVID-19, this paper provides health professionals with better accessibility to available evidence, summarising findings from a systematic overview of systematic reviews of the neurological symptoms seen in patients with COVID-19. Implications of so-called 'Long Covid' on neurological services and primary care and similarities with other neurological disorders are discussed. Methods: Firstly, a systematic overview of current reviews of neurological symptoms of COVID-19 was conducted. Secondly, the implications of these findings are discussed in relation to the potential effect on neurological services and the similarities in the experience of patients with COVID-19 and those with other neurological disorders. A total of 45 systematic reviews were identified within seven databases, published between 11 April 2020 and 15 October 2020, following a search in June 2020, updated on 20 October 2020. Results: The results indicated that COVID-19 exhibits two types of neurological symptoms; life-threatening symptoms such as Guillain-Barre Syndrome (GBS) and encephalitis, and less devastating symptoms such as fatigue and myalgia. Many of these so-called lesser symptoms appear to be emerging as longer-term for some sufferers and have been recently labelled Long Covid. When compared, these less devastating symptoms are very similar to other neurological conditions such as chronic fatigue syndrome (CFS) and functional neurological disorder (FND). Conclusion: Implications for neurological healthcare services in the United Kingdom (UK) may include longer waiting times and a need for more resources (including more qualified health professionals). There is also a possible change-effect on health professionals' perceptions of other neurological conditions such as CFS and FND. Future research is recommended to explore changes in health professionals' perceptions of neurological symptoms because of COVID-19.